An experimental study of wave scattering by a vertical slotted barrier in the presence of a current - Huang, Zhenhua (2013)
In coastal waters, tidal currents and surface waves co-exist. In this study, the influence of a steady current on the scattering of waves by a vertical slotted barrier is investigated experimentally in a wave flume. The separation of the incident and reflected waves is carried out by a two-point method that takes into account the effects of the current. Results show that currents significantly increase the wave-energy loss by the barrier and remarkably reduce the wave transmission through the barrier. It is suggested that the tidal currents should be taken into consideration in an economical design of slotted breakwaters.